Variation in spatiotemporal parameters and DoA of gait between transtibial and transfemoral amputees: a single centre study - Abdull Rasid, Mohd Zainizam; Nazrin, Mazehi; Omar, Batrisyia; Rosley, Nurhazalina; Wah, Tan Eng; Harith, Hazreen Haizi; Manaf, Haidzir; Bukry, Saiful Adli; Hussain, Hafez; Shapie, Azlan (Elsevier BV, 2024)
Limb loss presents significant challenges to mobility and quality of life, with prosthetic technology aiming to mitigate these impacts. Understanding the effects of amputation level on gait parameters is crucial for optimizing prosthetic design and rehabilitation strategies. While previous research has explored this relationship, the specific impact of amputation level on step width, step length, cadence, step time, and walking speed for both prosthetic and intact legs, as well as the degree of asymmetry in these parameters, remains underexplored. This study seeks to address this gap by comparing these parameters across different levels of amputation and assessing the degree of asymmetry, with implications for improving clinical outcomes and prosthetic interventions.